HAMKA’s concept of moderation an analysis - Abdullah, Fatimah; Adnan, Amira (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
Islam advocates balance between spiritual, emotional, and cognitive aspects of human life. Any imbalance between these aspects may tarnish the real image of Islam. Concentration on the informational and cognitive aspects of the religion and disregard of the endeavor towards excellence will create imbalance between ÊmÉn, islÉm and iÍsÉn. Likewise, Islam strikes a balance between individualism and collectivism. Man’s relationship with his Creator is the basis of moral attitude of man towards his fellow men namely, interpersonalrelationship. This is the real basis of Islamic morality or ethical system. Islam enjoins wisdom, balance, moderation and tolerance in all affairs. Moderation or balance is not only as general characteristic of Islam, but it is its fundamental landmark. This article attempts to analyze HAMKA’s Concept of Moderation based on his book “Falsafah Hidup” (Philosophy of life).